Synthesis and Characterization of Fe-Doped MCM-41 Using the One-Pot Method: XRD and FTIR Study - Fadly Yusup Yuday; Vera Pangni Fahriani (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
MCM-41 is a mesoporous solid material developed by Mobil Corporation, composed of amorphous silica with a regular pore structure and uniform pore size arranged in a hexagonal pattern. This material has a large surface area (700–1000 m2/g) and good thermal stability. MCM-41 is often used for the removal of heavy metals from aqueous media and as a heterogeneous catalyst to accelerate chemical reactions due to its flexible and modifiable nature. This study examines the effect of varying Fe metal doping on the one-pot synthesis of MCM-41 and its catalytic performance. MCM-41 was synthesized via a one-pot method using the following composition: 0.999 g CTAB, 4.666 g TEOS, 0.30 g NaOH, 1.245 g FeSO4, and 1.211 g FeCl3. Characterization of the synthesized material was performed using X-Ray Diffraction (XRD) for crystal structure analysis and Fourier Transform Infrared Spectroscopy (FTIR) for functional group identification; therefore, characterization of morphology and porosity is not discussed.